Investigação de mutações patogênicas em folículos dentários e tumores odontogênicos - Bruna Pizziolo Coura (2022)
Pathogenic mutations have been reported in several benign neoplasms, including odontogenic tumors. The molecular pathogenesis of mixed odontogenic tumors and adenoid ameloblastoma (AA) has not yet been elucidated. Mixed odontogenic tumors present epithelial and ectomesenchymal components proliferation. This group is composed by ameloblastic fibroma (AF), a benign neoplasm that is often a precursor of ameloblastic fibrosarcoma (AFS), ameloblastic fibrodentinoma (AFD) and ameloblastic fibro-odontoma (AFO), whose nature and classification are still a matter of debate, and odontomas, which are hamartomas. AA is an epithelial odontogenic tumor recently recognized as an entity. It shares microscopic overlapping with other odontogenic tumors, including ameloblastoma, which harbors BRAF p.V600E, and adenomatoid odontogenic tumor, which harbors KRAS mutation. The analysis of the genetic basis of these lesions could improve the knowledge about their molecular pathogenesis and help defining molecular markers for diagnostic purposes. Odontogenic tumors and cysts can originate from the dental follicle, which is an embryonic structure. However, there is little information about the molecular events that triggers tumorigenesis. Pathogenic mutations in tumor suppressor genes and oncogenes have been reported in normal tissues. Thus, the molecular analysis of dental follicle could lead to a better understanding of changes that occur in the early stages of odontogenic neoplasms and could assist indirectly in the prevention and directly in the early stages tumor detection. Therefore, the aim of this study was: 1) to investigate the profile of molecular changes in mixed odontogenic tumors, 2) to evaluate the pathogenic mutations in KRAS and BRAF in AA and 3) to investigate the mutational status of BRAF and KRAS genes in dental follicle associated with impacted teeth, since these mutations occur in a large proportion of ameloblastomas and adenomatoid odontogenic tumor. To achieve the first objective, a discovery cohort composed of mixed odontogenic tumors was sequenced by Next Generation Sequencing (NGS) using a hotspot mutation panel of 50 oncogenes and tumor suppressor genes. BRAF p.V600E was detected and confirmed by allele-specific real-time qPCR, and tested in a validation cohort, which included a total of 28 cases of mixed odontogenic tumors, with 22 being submitted to microdissection and laser capture, allowing to assess the status the mutational status of epithelial and mesenchymal components separately. The BRAF p.V600E pathogenic mutation was reported by the NGS in 2/4 samples from the discovery cohort. This mutation was detected in 4/10 (40%) AF, 3/4 (50%) AFD, 2/6 (33%) AFO and 2/3 (67%) AFS of the validation cohort, and it was found to be limited to the mesenchymal component in 7/9 mutation-positive cases. One case of AFS showed a remnant area of AF, with both mesenchymal components (AFS and AF) being positive for the mutation. Odontoma cases (5/5) were wild-type for the BRAF p.V600E mutation. To answer the second and third objectives, the BRAF p.V600E, KRAS p.G12V and p.G12R hotspot mutations were evaluated in a convenience sample of 9 AA and 48 dental follicles using allele-specific real-time qPCR. All cases of AA and dental follicle revealed wild-type status for BRAF p.V600E and KRAS p.G12V/R mutations. On the basis of the results, we conclude that AF, AFD, AFO and AFS present BRAF p.V600E in the mesenchymal component and that at least a subgroup of these lesions is molecularly distinct from odontomas. AA and dental follicles do not have BRAF p.V600E and KRAS p.G12V/R mutations, and if these do occur, they must occur at a very low frequency.